Skrining Potensi Essential Oil Cananga odorata dalam Penghambatannya Terhadap ACE II dan TMPRSS2 sebagai Anti Covid-19: Pendekatan In Silico - Yoni Rina Bintari; Dian Novita Wulandari (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
COVID-19 is a disease caused by viruses of the coronavirus class that are known to enter humans through the Angiotensin Coverting Enzyme (ACE II) receptor protein and transmembrane serine protease (TMPRSS 2). COVID-19 has become a pandemic, so it requires an agent that acts as an anti-Covid-19. Cananga odora is an herb that contains EO (Essential Oils) and is widely grown in Indonesia. EO are known to have antiviral potential.This study aims to explore the potential of EO from C.odora using a molecular docking approach by measuring its inhibition of ACE II (Q9BYF1) and TMPRSS2 (7MEQ). The inhibitory potential was calculated from the binding affinity using Pyrex Autodock Vina software. The docking results are then visualized using Biovia Discovery Studio and PyMOL. Prediction of physicochemical and pharmacokinetic profiles through pKCsm web. The docking results showed that geranyl acetate inhibited ACE II at Lys 562 with a gibs energy of -7.5 kcal. Thebest inhibition of TMPRSS2 by cedrole with energy gibs -6.2 kcal/mol via Pro 375. The active compound C. odorata has a different inhibitory mechanism from the control (chloroquine). The results of the in silico test predict the pharmacokinetic profile of EO from C.odora geranil asetat which has good absorption, distribution, metabolism and excretion values and is non-toxic, and cedrole can cross the blood brain barier.